MODERNISM ȘI TRADIȚIONALISM ÎN LIRICA LUI LUCIAN BLAGA - Paladian, Kristiniia (Чернівецький національний університет, 2020)
In the article the problem of classical forms in Lucian Blaga’s poetry with non-classical structure is tackled. It is shown that for the novelty in the structure of his oeuvres the poet referred to free usage of classic meters with a very shattered number of feet in the poem, sometimes simply playing with shorter and longer lines, placing them at random, adding syllables or a line. It has been found out that syllabo-tonic forms create unsymmetrical forms in the limits of one meter; heterorhythmic structures in the form of binary or ternary rhythms with free anacrusis, heterometric forms with the usage in one verse the lines written in different syllabo-tonic meters and heteromorphic constructions in which syllabo-tonic verses are combined with pure tonic forms.
Keywords: classical versification; modern versification; syllabo-tonic meters; free forms; heterorhythmic structures; heterometric forms; heteromorphic verse